2018
DOI: 10.1038/s41467-018-05425-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of CRISPR-Cas9 ribonucleoprotein into arthropod ovaries for heritable germline gene editing

Abstract: Cas9-mediated gene editing is a powerful tool for addressing research questions in arthropods. Current approaches rely upon delivering Cas9 ribonucleoprotein (RNP) complex by embryonic microinjection, which is challenging, is limited to a small number of species, and is inefficient even in optimized taxa. Here we develop a technology termed Receptor-Mediated Ovary Transduction of Cargo (ReMOT Control) to deliver Cas9 RNP to the arthropod germline by injection into adult female mosquitoes. We identify a peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(189 citation statements)
references
References 55 publications
2
162
0
Order By: Relevance
“…stephensi by ReMOT Control, we utilized the ovary targeting P2C peptide derived from Drosophila melanogaster yolk protein 1 (DmYP1), which we recently reported in Ae. aegypti to mediate delivery of Cas9 RNP into vitellogenic oocytes 8 . However, we found that the Aedes injection parameters were not directly translatable to An.…”
Section: Optimization Of Injection Components For Adult Injectionmentioning
confidence: 99%
See 3 more Smart Citations
“…stephensi by ReMOT Control, we utilized the ovary targeting P2C peptide derived from Drosophila melanogaster yolk protein 1 (DmYP1), which we recently reported in Ae. aegypti to mediate delivery of Cas9 RNP into vitellogenic oocytes 8 . However, we found that the Aedes injection parameters were not directly translatable to An.…”
Section: Optimization Of Injection Components For Adult Injectionmentioning
confidence: 99%
“…In previous work, we used chloroquine to facilitate exit of the Cas9 RNP from the endosome after uptake, but we noted that saponin (Quallaja bark extract) also could be used for this purpose (8). For…”
Section: Optimization Of Injection Components For Adult Injectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cas9) in complex with the gRNA, the socalled CRISPR-Cas9 RNA-protein complex (or ribonucleoprotein complex; RNP), which after uptake allows precise genome editing. Currently, efforts are made to deliver RNP complexes via virus-like particles, receptormediated endocytosis or osmocytosis (D'Astolfo et al, 2015;Liu et al, 2015;Yin et al, 2016;Chaverra-Rodriguez et al, 2018).…”
mentioning
confidence: 99%